Mainstreaming Islamic Moderations Values in Higher Education: Policy, Implementation, and Challenges - Titi Kadi (UIN Sultan Aji Muhammad Idris Samarinda, 2022)
Islamic moderation is highly vital in any field of life especially in higher educational context. In the context of this study, the researcher employed phenomenological study by the aim to investigate policy made by policy makers in two public universities in Balikpapan and Samarinda regarding the mainstreaming Islamic moderation in their universities by using in-depth interview. Additionally, the implementation of Islamic moderation was also explored especially on the steps of planning, implementing, and evaluating the teaching and learning process of Islamic Religious Education course or what so called by Pendidikan Agama Islam (PAI) course by utilizing direct observation, field-notes, and added by document analysis. Finally, in-depth interview was conducted to highlight the challenges faced by the PAI lecturers in mainstreaming Islamic moderation in PAI course. As a result, Islamic moderation was reflected in the policy made by the policy makers at both public universities in terms of hidden curriculum. Moreover, Islamic moderation values was also revealed in every aspect of teaching and learning of PAI course including planning, implementing, and evaluating. Lastly, the PAI lecturers encountered eight barriers when implementing Islamic moderation during PAI course. Novelty and pedagogical implications were also emphasized in this research.